2010
DOI: 10.1371/journal.pone.0012141
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors on Non-Dopaminergic Neurons in the VTA Support Cocaine Sensitization

Abstract: BackgroundThe initiation of behavioral sensitization to cocaine and other psychomotor stimulants is thought to reflect N-methyl-D-aspartate receptor (NMDAR)-mediated synaptic plasticity in the mesolimbic dopamine (DA) circuitry. The importance of drug induced NMDAR mediated adaptations in ventral tegmental area (VTA) DA neurons, and its association with drug seeking behaviors, has recently been evaluated in Cre-loxp mice lacking functional NMDARs in DA neurons expressing Cre recombinase under the control of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 34 publications
5
41
1
Order By: Relevance
“…However, we and others have shown that DAT:NR1 knockout mice also develop normal cocaine sensitization, similar to what we describe here (10,11,13). There are multiple possible explanations for this discrepancy.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, we and others have shown that DAT:NR1 knockout mice also develop normal cocaine sensitization, similar to what we describe here (10,11,13). There are multiple possible explanations for this discrepancy.…”
Section: Discussionsupporting
confidence: 85%
“…First, antagonists affect all cell types in a region, whereas the genetic approach allows only a particular cell type to be affected. Recent evidence strongly suggests that nondopaminergic cells in the VTA are the critical substrate in this region for mediating sensitization (13). Alternatively, it has been shown that not all dopamine neurons express DAT; therefore, Cre-mediated removal of Grin1 in DAT: NR1 knockout mice may be incomplete (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LTP in this area of the brain is otherwise known to occur after injection of cocaine (Ungless et al, 2001) and other drugs of abuse (Saal et al, 2003), and when inhibited in KO mice, causes alterations of drug-seeking behaviors (Engblom et al, 2008;Zweifel et al, 2008). Recent work has also revealed that LTP in nondopaminergic neurons of the VTA is even more directly linked to such drug-seeking behaviors (Luo et al, 2010). Therefore, understanding the mechanisms of LTP in the VTA may prove to be critical to our understanding of drug addiction.…”
Section: Introductionmentioning
confidence: 99%